Morphological and molecular characters reveal the status of Pedesta rubella (Devyatkin, 1996) stat. n. and P. similissima (Devyatkin, 2002) syn. n. (Lepidoptera, Hesperiidae) - Li, Meng; Monastyrkii, Alexander L.; Kolesnichenko, Kirill A.; Liu, Zihao; Xue, Guoxi; Long, Jifeng; Tang, Huaxing (Zootaxa, 2020)
To clarify the relationships of Pedesta submacula (Leech, 1890), P. submacula rubella (Devyatkin, 1996) and P. similissima (Devyatkin, 2002), specimens from various localities in China and Vietnam, including the type materials of P. submacula rubella and P. similissima were examined. A neighbor-joining (NJ) tree was also reconstructed based upon partial COI sequences of 24 ingroup specimens and 4 outgroup species. The result shows that P. similissima is a synonym of P. submacula, and P. submacula rubella belongs to a separate species. The mean Kimura-2-Parameter genetic distance between P. submacula and P. rubella stat. n. is 4.4%. Wing patterns and genitalic structures of these taxa are illustrated and compared. A distribution map of both species is provided.